Impact of feeding cover crop forage containing brassicas to steers during backgrounding on live animal performance, carcass characteristics, and meat color1. Issue 3 (23rd July 2021) - Bakker, Christina E; Hite, Lydia M; Wright, Cody L; Brake, Derek W; Smart, Alexander J; Blair, Amanda D; Grubbs, Judson K; Underwood, Keith R
Abstract: Brassica cover crops are an option for producers to incorporate into their cropping system to improve soil health and also provide a feed resource for cattle. While brassica cover crops have been widely used for grazing cows, their use as a backgrounding feedstuff is relatively unknown. The objective of this study was to determine the impact of feeding a brassica cover crop mixture during backgrounding on live animal performance and carcass characteristics. A total of 30 Angus-based steers were assigned to one of two dietary treatments during backgrounding 1) ad libitum access to a diet containing freshly cut brassica cover crop forage (CC) containing radish, turnip, rapeseed, rye grass, and a liquid supplement or 2) common Midwestern dry lot growing diet containing silage, soybean meal, grass hay, and a liquid supplement (CON). Steers were assigned to electronic feed bunks (Insentec RIC, Hokofarm Group; Marknesse, the Netherlands) for collection of individual feed intake. Diets were formulated to be nutritionally similar on a dry matter basis. Steers were paired by weight across treatments and pair fed. Dry matter intake (DMI) was calculated daily for steers in the CC treatment and the following day, CON steers were allowed access to an equal amount of dry matter using the Insentec RIC system. Steers were weighed weekly and backgrounded for 44 days before transitioning to a common finishing diet and weighed every 28 days. Steers were harvested at an estimated average backfat thickness of 1 cm. Standard carcass data were measured and strip loins and shoulder clods were collected. Instrumental and subjective color were measured on ground beef for 8 days and instrumental color was measured on strip steaks for 11 days. Treatment did not influence carcass characteristics, average daily gain, and DMI ( P > 0.17). However, CON steers exhibited increased gain to feed ratio ( P = 0.02). Additionally, a treatment by day interaction was observed for ground beef discoloration as the CC treatment displayed increased discoloration on days 4, 6, and 7 of case life ( P < 0.01). These data indicate that brassicas may be utilized in a backgrounding diet without negatively impacting carcass characteristics but may decrease case life of ground beef.